2019
DOI: 10.1155/2019/7857082
|View full text |Cite
|
Sign up to set email alerts
|

Irisin Contributes to the Hepatoprotection of Dexmedetomidine during Intestinal Ischemia/Reperfusion

Abstract: Intestinal ischemia/reperfusion (I/R), which is associated with high morbidity and mortality, is also accompanied with abnormal energy metabolism and liver injury. Irisin, a novel exercise-induced hormone, can regulate adipose browning and thermogenesis. The following study investigated the potential role of dexmedetomidine in liver injury during intestinal I/R in rats. Adult male Sprague–Dawley rats underwent occlusion of the superior mesenteric artery for 90 min followed by 2 h of reperfusion. Dexmedetomidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 52 publications
2
38
0
Order By: Relevance
“…Intestinal I/R injury is associated with increases in luminal epithelial permeability and ingress of bacterial molecules (e.g., enterotoxin) or bacteria themselves which can result in systemic inflammatory responses, multiple organ failure, and even leading to death [1][2][3]. In the present study, Chiu's score, the W/D ratio of intestine, and serum DAO activities increased, indicating that intestinal I/R injury caused a great damage to the intestine, and the model was successfully established [4,6,22]. The present results also demonstrated that HRS could attenuate intestinal injury, as evidenced by Mediators of Inflammation the improved morphological changes and survival rate.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…Intestinal I/R injury is associated with increases in luminal epithelial permeability and ingress of bacterial molecules (e.g., enterotoxin) or bacteria themselves which can result in systemic inflammatory responses, multiple organ failure, and even leading to death [1][2][3]. In the present study, Chiu's score, the W/D ratio of intestine, and serum DAO activities increased, indicating that intestinal I/R injury caused a great damage to the intestine, and the model was successfully established [4,6,22]. The present results also demonstrated that HRS could attenuate intestinal injury, as evidenced by Mediators of Inflammation the improved morphological changes and survival rate.…”
Section: Discussionsupporting
confidence: 49%
“…Intestinal I/R injury model was established as described previously [4,6]. Briefly, the rats were fasted for 12 h, with free access to drinking water before surgery.…”
Section: I/r Model and Hrs Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have revealed that irisin improves mitochondrial function, reduces ROS production and provides organ protection in various diseases, including Alzheimer's disease, pancreatitis and I/R‐induced intestine, lungs, brain, heart, liver injury (Bi et al, 2020; Bi, Zhang, Ren, Du, Li, Wang, Wei, et al, 2019; Chen et al, 2017; Du et al, 2019; X. Fan, Du, et al, 2019; Lourenco et al, 2019; Ren et al, 2019, 2020; H. Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%